Case report: Treatment-resistant depression with acute psychosis in an adolescent girl with Cushing's syndrome - Yin, Xiaowen; Chen, Song; Ju, Xuan; Hu, Xiwen (Frontiers in Psychiatry, 2023)
Cushing’s syndrome (CS) is a rare disease with multiple somatic signs and a high prevalence of co-occurring depression. However, the characteristics of depression secondary to CS and the differences from primary major depression have not been described in detail. In this case, we report a 17-year-old girl with treatment-resistant depression with a series of atypical features and acute psychotic episodes, which is a rare condition secondary to CS. This case showed a more detailed profile of depression in CS and highlighted the differences with primary major depression in clinical features, and it will improve insight into the differential diagnosis especially when the symptoms are not typical.